Status of respectful maternity care among postnatal women availing delivery services at a tertiary care centre: a cross-sectional study - Samal, Rupal; Padmanaban, Nikithaa; Sulochana, Raj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: There are numerous reports of disrespectful, abusive, or neglectful treatment during childbirth from health facilities. Although India has substantially increased the number of hospital deliveries, the quality of intrapartum and immediate postpartum care for delivering mothers has not given much importance. Therefore, assessing mistreatment and quality of care during childbirth is vital for promoting respectful maternity care (RMC). Aim and objectives were to assess the status of RMC in tertiary care centre and to assess and compare various domains of RMC. Methods: The cross-sectional study was conducted in the division of obstetrics and gynaecology, with 170 patients were enrolled and standard set of validated questionnaires was given to assess the RMC and socio-demographic status with appropriate statistical evaluation Results: Data was collected using a predesigned and pretested questionnaire based on seven major categories as per the RMC. Results showed that 100% experienced at least one form of disrespect during their labor, childbirth, or postnatal period at the hospital. Conclusions: The study sheds important light on the current state of RMC wherein mothers are noticing and reporting positive changes in maternity care, RMC still has scope of optimization in certain domains.